Variasi Molaritas H2SO4 pada Polianilin/H2SO4 - Moch. Nur Chomari; Diah Hari Kusumawati (Sains dan Matematika, 2012)
Synthetis of polyaniline has carried out using oxidation polymerization of aniline monomer to oxidant ammonium peroxydisulfat (NH)4S2O8 and H2SO4 as a source of proton doped. Variations in the molarity of H2SO4 conducted to determine of optimum polyaniline on electrical conductivity. Polyaniline samples were characterized by FTIR to determine the cluster function and the four-point probe method to determine the electrical conductivity. FTIR results showed that the samples were synthesized is polyaniline. Electrical conductivity test by used four point probe method showed higher acid molarity higher the electrical conductivity to the optimum. After reaching the optimum point, the electrical conductivity of polyaniline decreases followed by the molarity increases. Polyaniline has the most optimum conductivity of 1.833 S/cm when synthesized with 0.12 M H2SO4.